Wireless electronic notice board - Zohedi, Fauzal Naim (2007)
This project is designed to develop a Wireless Electronic Notice Board. It is widely used to display latest information anywhere such as faculty, shop, mosque and other places. This Wireless Electronic Notice Board offers the flexibility to user to control the information display within 25m range. The information is transmitted using RF as wireless technique. The Wireless Electronic Notice Board consists of two module; transmitter and receiver module. There are five parts in transmitter module and four parts in receiver module. In transmitter module, there are keypad, Liquid Crystal Display (LCD), Microcontroller, encoder and transmitter. In receiver module there are receiver, decoder, microcontroller, and dot matrix. This project is based on MC68HC11A1 microcontroller. Assembly language is used to program the microcontroller.